CONTENT AND FACE VALIDITY ANALYSIS ON 9TH GRADE’ FINAL TEST ITEMS FOR SECONDARY SCHOOL LEVEL - Zuhairoh, Zuhairoh; Syafa'ah, Nailisy; Kurniati, Diah (Prominent, 2024)
In English language teaching process, assessment has an important tool for examining the students’ skill and knowledge. The results of the teaching and learning process must be evaluated by teachers. During the assessment, the teacher can collect information or have the pictures explained. Curriculum in SMP is using 2013 curriculum. It needs to be evaluated in content and face validity. The objectives of the research are to identify content validity and face validity analysis on 9th grade’ final test items for secondary school level. The methodology used to perform this study was descriptive qualitative. The test's content validity was assessed using the qualitative analysis. Data collection for this study used the documentary analysis approach. The writers examine the validity of the content using the specification table and the English curriculum for grade 9 before calculating each item's number according to the competencies and indicators. While analyzing facial validity, the author used an English test file. Findings of this research showed that all of the items tested are covered in the indicators and competencies based on the table specification and English syllabus.